Co-designing a local language learning program for indigenous youth: a linguistic sustainability initiative - Tiurma Putri (Indonesian Journal of Applied Community Research, 2026)
Background: Indonesia’s Indigenous languages face increasing decline among youth due to limited intergenerational transmission and marginalization within formal education, necessitating community-based revitalization initiatives. Objective: This program aimed to co-design a local language learning model to strengthen Osing language use, confidence, and sustainability among Indigenous youth in Banyuwangi, East Java. Method: A participatory approach was implemented involving youth, cultural elders, teachers, and local institutions through workshops, practice-based learning, mentoring, and mixed-method evaluation. Results: The program increased active oral use of the Osing language, improved speaking confidence, and fostered positive language attitudes, alongside the emergence of youth-generated materials and language clubs supported by institutional endorsement and intergenerational collaboration. Implication: These findings suggest that community-driven, participatory models can effectively revitalize Indigenous languages by fostering youth engagement and sustainable intergenerational transmission. Novelty: The program introduces a co-design-based model that integrates youth agency, linguistic sustainability, and low-cost community empowerment as a scalable strategy for local language revitalization.